Analisis Gender Program Pemberdayaan Integrasi Kakao-Kambing PE di Taman Teknologi Pertanian Nglanggeran - Siti Andarwati; Dina Ruslanjari; Nurhayati (Pusat Studi Wanita dan Keluarga UGM, 2023)
Gender issue is one of the main issue in national development implementation especially the development of human resources. The government has done many empowerment programs with expectation to improve the quality of society especially woman, but data shows that there is still asymmetry between man and woman in many activities, access, and control into resources and development benefit. This research intends to analyze public-empowerment activity within Etawah Crossbreed Cocoa-Goat Integration Program in Gender Perspective. The research information consists of man and woman constituting couple (husband-wife) and gets involved as empowerment program. This research used qualitative method through observation technique, in-depth interview with documentation and literature. The results of research show that there is still gender asymmetry in development program implementation especially woman. The expectation of empowerment program implementation can decide job decision received by man and woman and doing knowledge transfer activity in domestic development. Activity, access, and control into resources and development benefit are affected by supporting idea such as social, education, and globalization, as for resistor idea such as population structure, economic, politics, and culture.